Targeted Covalent Inhibitors for the Treatment of Malaria? - Kulkarni, Shashank; Urbahns, Klaus; Spangenberg, Thomas (ACS infectious diseases, 2020)
Malaria is a vector-borne disease caused by protozoan parasites of the genus . According to the World Health Organization, it is one of the most serious infectious diseases threatening more than 3 billion people worldwide. In recent years, targeted covalent inhibitors (TCIs) have gained a lot of attention and several TCI-based drugs have been approved across different therapeutic areas. For malaria, surprisingly, this approach has not been explored in depth even though lot of advancements have been made in understanding the biology of the parasite. Herein, we present our views on exploring TCIs as a new class of antimalarial agents.